PEMETAAN PROFIL GURU GEOGRAFI SMA SE KABUPATEN PASAMAN - Fadhilah, Fadhilah; Anwar, Syafri (JURNAL BUANA, 2023)
This study aims to: 1) To obtain information about the distribution and number of geography teachers in each high school in the Pasaman Regency area, 2) To find out what self-development teachers have participated in by high school geography teachers in Pasaman Regency from 2014-2019, 3 ) To find out what scientific publications were published by high school geography teachers in Pasaman Regency from 2014-2019. 4) To find out what innovative works have been produced by high school geography teachers in Pasaman Regency. The method used in this research is a survey method. In surveys, information is collected from respondents using a census-distributed questionnaire or questionnaire. In general, survey research is described as scientific research in which data are collected from a selected sample of the entire population. Based on the research that has been done, it can be concluded that the following conclusions can be drawn: 1) The general identity condition of high school geography teachers in Pasaman Regency is quite good, because almost all high school geography teachers in Pasaman Regency have a minimum education/last education degree, which means they have met the criteria. minimum that has been stipulated in PP No. 32 of 2013; 2) The self-development of high school geography teachers in Pasaman Regency is still relatively low. Most of the high school geography teachers in Pasaman Regency still have not followed their self-development; 3) The scientific publication of high school geography teachers in Pasaman Regency is still very low; 4) There are no innovative works produced by high school geography teachers in Pasaman Regency.